Visual exploration of microbiome data (vol 44, 119, 2019) - Kuntal, Bhusan K.; Mande, Sharmila S. (Journal of Biosciences, 2020)
In the October 2019 Special Issue of theJournal of Bioscienceson Current Trends in Microbiome Research, in the Review article titled `'Visual exploration of microbiome data'' by Bhusan K. Kuntal and Sharmila S. Mande (DOI: 10.1007/s12038-019-9933-z; Vol. 44, Article No. 119), affiliation 3 for Bhusan K. Kuntal was incorrectly mentioned as `'Academy of Scientific and Innovative Research, CSIR-National Chemical Laboratory Campus, Pune 411008, India''. The correct affiliation should read as `'Academy of Scientific and Innovative Research (AcSIR), Ghaziabad 201 002, India''.